From conflict of use to multiple use: forest management innovations by small holders in Amazonian logging frontiers - Shanley, P.; Serra Silva, M. da; Melo, T.; Carmenta, R.; Nasi, Robert (2011)
The Brazilian Amazon is a significant source of timber as well as a rich source of non-timber forest products (NTFPs) such as medicinal barks, oils and fruits. Lack of quantity, quality, uniformity and price as well as a lack understanding of NTFPs socioeconomic, cultural or spiritual value and function in societies relegates them to a marginal economic status eclipsed by timber. The data vacuum for most NTFPs is contrasted by the large amount of timber-specific data available for many logged species. Such data sources can offer insights into the extraction level and locations of a subset of species that are valued for both timber and NTFPs. These are referred to as ‘conflict-of-use’ species. In this article we examine three such species, focusing on the Amazonian state of Pará. Pará is situated in the Brazilian “arc of deforestation” and the state accounts for 47% of all timber produced in the Legal Amazon. We describe three highly-utilized Amazonian NTFPs currently logged commercially: (1) Cumuru, Dipteryx odorata, which bears a seed yielding an essential oil employed in the perfume industry and providing income and medicine to rural families; (2) Amapá amargoso, Parahancornia fasciculata, which produces a powerful exudate used as a treatment of respiratory diseases; and (3) Uxi, Endopleura uchi, which produces a nutritious fruit consumed by humans and wildlife. We analyze data from the timber industry indicating the rate of extraction of these species, as well as data regarding their use and value as NTFPs. Results indicate that extraction of these species in logging frontiers contributes to declining access. However, in communities with links to markets, undocumented management systems supply the increasing demand for NTFPs in urban areas. While there are no formal management plans for these species and few scientific attempts made to manage them, small holders have developed local knowledge and innovative techniques to improve productivity, increase density and create multiple-use systems in the face of growing land use pressures.